Autotransplantation of a Third Molar to Replace Compromised Molar With the Individual Three-Dimensional Printed Ultrasonic Osteotome: A Case Report - Cheng Bi; Wen Zhang; Bin Peng (Case Reports in Dentistry)
Tooth autotransplantation is widely used to replace congenitally missing teeth or teeth with irreversible damage. This case report presents a personalized ultrasonic osteotome that enables precise preparation, minimizes bone trauma, enhances the initial stability of the transplanted tooth, and contributes to a favorable prognosis. The procedure is as follows: a 25-year-old female patient presented with a porcelain-fused-to-metal crown on Tooth #19, which had detached due to severe decay, rendering the tooth unsalvageable. Tooth #32 exhibited mesial inclination, resulting in decay of Tooth #31. After presenting treatment plan, the patient provided informed consent by signing the necessary documentation to proceed with the autotransplantation of Tooth #32 to replace Tooth #19. Tooth #32 was extracted and immediately scanned chairside using a 3Shape scanner. A custom-designed, tooth root–shaped ultrasonic osteotome was fabricated using 3D printing technology to match the shape of Tooth #32. Tooth #19 was extracted using a minimally invasive technique. The alveolar socket of Tooth #19 was prepared using the customized 3D-printed ultrasonic osteotome and a computer-aided rapid prototyping resin model. Tooth #32 was then transplanted into the socket and secured with figure-eight suspension sutures. To prevent damage to bone cells and periodontal tissues from overheating during socket preparation, the ultrasonic osteotome was designed with a porous, water-cooled system, effectively addressing this issue. After 24 months of follow-up, the transplanted tooth met success criteria, with no signs of pathological radiolucency, root resorption, or pain in the donor tooth. The alveolar socket, prepared with the personalized ultrasonic osteotome, ensured an optimal fit for the donor tooth, maintaining its stability and minimizing postoperative complications. The use of 3D printing technology to create a personalized ultrasonic osteotome represents an innovative advancement in tooth transplantation, supporting the development of digital and minimally invasive techniques in this field.